2014
DOI: 10.3892/mmr.2014.1941
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of a methanol extract from Ardisia tinctoria on mouse macrophages and paw edema

Abstract: Ardisia tinctoria (AT) is a plant of the Myrsinaceae family. No studies on its anti-inflammatory effects have yet been reported. This study investigated the anti-inflammatory activity of AT. A non-cytotoxic methanol extract of AT inhibited the expression of inducible NO synthase (iNOS) and cyclooxygenase-2 (COX-2), leading to significantly reduced levels of nitric oxide (NO) and prostaglandin E2 (PGE2) and of two proteins regulated by these, interleukin-1β (IL-1β) and IL-6, in lipopolysaccharide (LPS)-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Among the many pro-inflammatory mediators, NO and PGE 2 play key roles in inflammatory reactions (28,29). NO is Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many pro-inflammatory mediators, NO and PGE 2 play key roles in inflammatory reactions (28,29). NO is Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is a potent activator of macrophages, and the activated macrophages produce a variety of proinflammatory molecules, including prostaglandin E 2 (PGE 2 ) and nitric oxide (NO). Among these molecules, inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) are the proinflammatory enzymes necessary for inflammation, and they produce the proinflammatory mediators NO and PGE 2 , respectively [3]. Moreover, LPS stimulation also leads to the generation of inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-(IL-) 6 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that pro-inflammatory mediator expression is regulated by phosphorylation of MAPK family mediators such as ERK 1/2, p38, and JNK (Park et al, 2012). It is well known that LPS drives intracellular signaling pathways such as MAPKs (Kim et al, 2014). Cigarette smoke condensate (CSC) is a strong inducer of the phosphorylation of MAPKs.…”
mentioning
confidence: 99%